A alfabetização científica dos professores dos anos iniciais do ensino fundamental na perspectiva da teoria da aprendizagem significativa - Silva, Bruno Rogério Duarte da (2008)
This study discusses the "years of Scientific Literacy of the teacher starting with the elementary school ". It aims to critically analyze the scientific literacy within the practice teaching of the teacher/trainee starting from elementary school. The study is based on the theory of significant learning and raises a new perspective on the progress of the teaching, learning, and the significance relating to the students of the pedagogy course. This is in relation to the teaching of natural sciences, in order to identify the elements capable of contributing to effective renewal in training of teachers. Such research is based on Ausubel and Moreira, Chassot, Hernandéz and others. The search for embossing a qualitative research is the type of action that took place in a Public School Hall of Palmeira dos Indios, which is the locus Stage Supervised Practice of Teaching in the years starting from elementary school, the course of Pedagogy of the School of Science Human and Economic of Palmeira dos Indios. We examined four teachers/trainees who developed projects to work on scientific topics in classes from 1st to 4th grade of elementary school. The projects used questionnaires, portfolios, reports of meetings and interviews as instruments of research. They investigated the teaching, field of scientific content reports of characterization, observation, portfolios (terms of record with all shares held by the students on stage text, photos, activities, testimonials, etc.) and their work projects. Then it happened the socialization experiences, seminars, deepening theoretical and conceptual construction of maps. The work of research contributed in a meaningful way to the construction of knowledge about the teaching practice. There is a need for scientific literacy and understanding of the theory of learning significant criticism in Alagoas. However, due to lack of a significant learning of the content of natural sciences in school, it is confirmed the hypothesis that the use of the methodology of work projects on practice teaching, involving scientific themes, can mean learning in the natural sciences for the teachers of the early years of primary school. Thus, will raise their scientific literacy.